Le Pragmatisme De Rorty : Entre Universalisme Et Relativisme - Médégnon, Désiré (European Scientific Journal, ESJ, 2017)
Philosophy and science became what they are and developed because they have taken the universal both as the goal of research and the criteria of validity of every theory. For Richard Rorty, we have there a project with no foundation and totally unjustified. To Plato’s universalism, Rorty opposes a pragmatism which defends philosophy as fitting as human being and considers that the only reasonable goal of research is to come to intersubjective agreements. In spite of the fact that it is difficult for science to get used to it, pragmatism has nevertheless done the great job of unveiling the illusion of an objective truth conceived as the speculum of reality.